CULTURAL RESILIENCE AND CULTURAL PRESERVATION STRATEGIES IN MAINTAINING THE NATION'S IDENTITY - Habibi, Ahmad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
A culture-defending strategy is essential to preserve and strengthen the nation's identity amidst the accelerating pace of globalization. In the Indonesian context, cultural diversity, which includes customs, languages, arts and traditions, needs to be protected in order to remain as a strong foundation for the nation's progress. Cultural resilience can be achieved through strengthening cultural education, preserving cultural heritage, and increasing public awareness of the importance of protecting local values. The use of information technology and social media can serve as effective tools in disseminating Indonesian culture to the younger generation and the international community. In addition, cooperation between the government, the community, and the private sector is needed to formulate policies that support cultural preservation and avoid cultural uniformity. With the right cultural resilience approach, the nation's identity will be maintained, fostering pride and encouraging unity amidst differences. Cultural resilience is not just about maintaining what already exists, but also encouraging the creation of cultural values that are relevant and adaptable to changing times. This is the key to maintaining the existence and unity of the nation in a challenging global era.